Positive Psychological Assessment: A Handbook of Models and Measures (2nd Ed.). 2019
DOI: 10.1037/0000138-015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring emotional and personal intelligence.

Abstract: However, the 20th century has seen a debate as to whether general intelligence-the capacity to reason abstractly and acquire knowledge-is more important than an intelligence with a narrower focus, a type of intelligence called broad intelligence. The concept of general and broad intelligences comes from the Cattell-Horn-Carroll model, which posits three levels or "strata" of intelligence. Stratum 3 is general intelligence, labeled g, followed by a series of what are labeled broad intelligences (e.g., fluid rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
5
0
5
Order By: Relevance
“…TEI is composed of three dimensions and can be defined as the ability to attend (emotional attention), understand (emotional clarity), and modify (mood repair) emotional states ( Salovey et al, 1995 ). Many studies have confirmed the role of TEI as a predictor of positive emotional states and personal, social, academic, and work success ( Brackett et al, 2011 ; Caruso et al, 2019 ; Guil et al, 2019 ). Research has also shown how emotions and affective states control our health and well-being ( Vera-Villarroel et al, 2019 ; Sarrionandia and Mikolajczak, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…TEI is composed of three dimensions and can be defined as the ability to attend (emotional attention), understand (emotional clarity), and modify (mood repair) emotional states ( Salovey et al, 1995 ). Many studies have confirmed the role of TEI as a predictor of positive emotional states and personal, social, academic, and work success ( Brackett et al, 2011 ; Caruso et al, 2019 ; Guil et al, 2019 ). Research has also shown how emotions and affective states control our health and well-being ( Vera-Villarroel et al, 2019 ; Sarrionandia and Mikolajczak, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…In 1983, Howard Gardner introduced eight different types of intelligences, two of them, interand intra-personal intelligences constituting EI. The term 'Emotional Intelligence' was coined in 1990 by two researchers, Peter Salovey and John Mayer who defined EI is 'a subset of social intelligence that involves the ability to monitor one's own and others' feelings and emotions, to discriminate among them and to use this information to guide one's own thinking and actions' (Caruso, et al, 2019). EI was later popularized by Daniel Goleman in his 1995 book.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Therefore, there is a lack of studies that collect, with a wide review coverage, the instruments developed in recent years. The few reviews that can be found [ 16 , 17 , 18 , 19 ] are limited to describing both the most popular measures (e.g., Mayer–Salovey–Caruso Emotional Intelligence Test [MSCEIT], Emotional Quotient Inventory [EQ-i], Trait Meta-Mood Scale [TMMS], Trait Emotional Intelligence Questionnaire [TEIQue], or Schutte Self-Report Inventory [SSRI]) and those validated only in English, producing an apparent “Tower of Babel” effect (i.e., the over-representation of studies in one language and the under-representation in others) [ 20 ]. This is a problem that is not only more common than is believed, but it is also persistent [ 21 ].…”
Section: Introductionmentioning
confidence: 99%